COMMUNITY-BASED DISASTER COMMUNICATION IN THE EMERGENCY RESPONSE PHASE OF THE ERUPTION OF MOUNT LEWOTOBI MEN, EAST FLORES - Hidayat, Muhamad; Ananto Akbar (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
East Flores is an area in Indonesia that is prone to various types of natural disasters, one of which is the volcanic eruption disaster. The Center for Volcanology and Geological Disaster Mitigation (PVMBG) released data on the status of the Male Lewotobi Volcano in Wulanggitang District, East Flores Regency, East Nusa Tenggara (NTT) upgraded from Level III or Alert to Level IV or Alert since January 9, 2024 at 23.00 WITA. Disaster management in the emergency phase requires the active role of the community or community in disaster communication efforts. Muhammadiyah Disaster Management Center (MDMC) Sikka Regency is one of the community organizations that plays an active role in helping to handle the disaster of the eruption of Lewotobi Laki Volcano. This study aims to analyze and describe the communicationmanagement during emergency response carried out by MDMC Sikka Regency. Data collection is carried out by qualitative methods such as: interviews, observations, documentation and Focus Group Discussion (FGD). The results ofthe study found that in the disaster emergency phase, the importance of the role of the community in assisting the disaster management process as carried out byMDMC Sikka Regency during the emergency disaster of the eruption of Mount Lewotobi Laki in East Flores.